2017
DOI: 10.1177/0363546517735844
|View full text |Cite
|
Sign up to set email alerts
|

Intra-articular Mesenchymal Stem Cell Therapy for the Human Joint: A Systematic Review

Abstract: This review provides strong evidence that autologous intra-articular MSC therapy is safe, with generally positive clinical outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
92
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(98 citation statements)
references
References 50 publications
1
92
0
5
Order By: Relevance
“… 56 Recent clinical trials showed a decrement of pain, an enhancement of joint performance, and a high quality of cartilage repair in knee OA, following MSC treatment. 57 Exosomes were also shown to be involved in the IBDs, which are a set of chronic disorders that occur when intestinal homeostasis is impaired. 12 One of the many mechanisms underlying these diseases is represented by the immune response modulated by macrophage activity.…”
Section: Exosomes In Different Chronic Pain Conditionsmentioning
confidence: 99%
“… 56 Recent clinical trials showed a decrement of pain, an enhancement of joint performance, and a high quality of cartilage repair in knee OA, following MSC treatment. 57 Exosomes were also shown to be involved in the IBDs, which are a set of chronic disorders that occur when intestinal homeostasis is impaired. 12 One of the many mechanisms underlying these diseases is represented by the immune response modulated by macrophage activity.…”
Section: Exosomes In Different Chronic Pain Conditionsmentioning
confidence: 99%
“…When combined with the reality that existing treatment options are often suboptimal for many soft‐tissue injuries and that many patients seeking treatment are frequently relatively young and desirous of returning to an active lifestyle, an environment has been created in which patients are vulnerable and will seek such stem/progenitor cell treatments. However, although great potential exists for the use of cell‐based approaches to improve tissue healing and regeneration, the reality is that current data for the use of cell‐based therapies for augmentation of tissue healing is highly variable …”
Section: Key Question 5: What Are the Task Force Recommendations For mentioning
confidence: 99%
“…However, although great potential exists for the use of cell-based approaches to improve tissue healing and regeneration, the reality is that current data for the use of cell-based therapies for augmentation of tissue healing is highly variable. 111,112 Given this significant limitation, it is imperative that patients are informed that there exists little highlevel animal model or randomized clinical trial data to support the use of stem/progenitor cell-based approaches for tissue healing. It should also be communicated to patients that use of these treatment approaches are most often off-label, and that the treating facility often has a financial incentive to perform a stem/progenitor cell procedure which is unlikely to be covered by standard medical insurance.…”
Section: Cell-based Therapy In Humansmentioning
confidence: 99%
“…While developments in stem cell therapy display the potential to regrow cartilage, the current body of work is comprised of poorquality evidence with widespread heterogeneity, a lack of reproducibility, and gaps in translating in vitro and preclinical findings to patient care. 84,85 By far, the most widely studied growth factor related treatment is platelet-rich plasma (PRP). PRP is produced by high-speed centrifugation of blood that leads to a supernatant with a platelet concentration well above baseline.…”
Section: Regenerative Medicinementioning
confidence: 99%